Positronium ionization by short UV laser pulses: Splitting of the ATI peaks by Rabi oscillations - Rodríguez Chariarse, Vladimir Daniel (2006)
The interaction between positronium and a short laser pulse is studied in the case, where the photon energy is resonant with the 1s → 2p transition energy. Results from a full numerical solution of the time-dependent Schrödinger equation, and also from a variational approach based on the Coulomb-Volkov wave function to describe the final states are presented. For the initial state, a solution of the time-dependent Schrödinger equation involving the two resonantly bound states is used. This wave function exhibits Rabi oscillations as the laser amplitude increases. Using the rotating wave approximation the contribution from N-photon and (N - 1)-photon ionization from ground and excited state with split energy levels can be identified. The theory predicts each above threshold ionization primary peak split in two peaks separated by half an appropriate Rabi frequency. It is suggested that this phenomenon could be experimentally measured by the Aarhus group working on positronium in laser fields. © 2006 Elsevier B.V. All rights reserved.